Production potential and stability of hydrate-bearing sediments at the site GMGS3-W19 in the South China Sea: A preliminary feasibility study. (September 2017) - Sun, Jiaxin; Zhang, Ling; Ning, Fulong; Lei, Hongwu; Liu, Tianle; Hu, Gaowei; Lu, Hailong; Lu, Jingan; Liu, Changling; Jiang, Guosheng; Liang, Jinqiang; Wu, Nengyou
Abstract: According to the preliminary geological data of gas hydrate bearing-sediments (GHBS) at site GMGS3-W19 in the third Chinese expedition to drill gas hydrates in 2015, a production model using three different recovery pressures was established to assess the production feasibility from both production potential and geomechanical response. The simulation results show that for this special Class 1 deposit, it is a little hard for gas production rate to reach the commercial extraction rate because the degree of hydrate dissociation is limited due to the low reservoir permeability and the permeable burdens. However, the free gas accumulating in the lower part of the GHBS can significantly increase gas-to-water ratio. It also generates many secondary hydrates in the GHBS at the same time. Decreasing the well pressure can be beneficial to gas recovery, but the recovery increase is not obvious. In term of geomechanical response of the reservoir during the gas recovery, the permeable burdens are conducive to reduction of the sediment deformation, though they don't facilitate the gas recovery rate. In addition, significant stress concentration is observed in the upper and lower edges of GHBS around the borehole during depressurization because of high pressure gradient, and the greater the well pressure drop, the more obvious the phenomenon. Yield failures and sand production easily take place in the edges. Therefore, in order to achieve the purpose of safe, efficient and long-term gas production, a balance between the production pressure and reservoir stability should be reached at the hydrate site. The production pressure difference and sand production must be carefully controlled and the high stress concentration zones need strengthening or sand control treatment during gas production. Besides, the sensitivity analyses show that the hydrate saturation heterogeneity can affect the production potential and geomechanical response to some extent, especially the water extraction rate and the effective stress distribution and evolution. Increasing GHBS and its underlying free gas formation permeabilities can enhance the gas production potential, but it probably introduces geomechanical risks to gas recovery operations. Highlights: Gas production potential for the latest hydrate reservoir in China was reported. Reservoir stability of the hydrate deposits at three recovery pressures was analyzed. The potential risk area of sand production during depressurization was revealed. The optimal balance between gas production and reservoir stability was suggested. The effects of main geologic parameters on production response were revealed.